REVIEW AND RECOMMENDATIONS ON MANAGEMENT OF ADULT FEMALE THALASSEMIA PATIEΝTS WITH HYPOGONADISM BASED ON LITERATURE REVIEW AND EXPERIENCE OF ICET-A NETWORK SPECIALISTS - Vincenzo De Sanctis (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Multi-transfused thalassemia major (TM) patients frequently develop severe endocrine complications, mainly due to iron overload, anemia and chronic liver disease, which require prompt diagnosis, treatment and follow-up by specialists.